2019
DOI: 10.1186/s12929-019-0503-3
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian strains of Toxoplasma gondii are controlled by azithromycin and modulate cytokine production in human placental explants

Abstract: BackgroundToxoplasma gondii is a protozoan parasite that causes congenital toxoplasmosis by transplacental transmission. Parasite strains are genetically diverse and disease severity is related to the genotype. In Uberlândia city, Brazil, two virulent strains were isolated: TgChBrUD1 and TgChBrUD2. Congenital toxoplasmosis is more prevalent in South America compared to Europe, and more often associated with severe symptoms, usually as a result of infection with atypical strains.MethodsConsidering that T. gondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 67 publications
0
9
0
4
Order By: Relevance
“…It was demonstrated by www.nature.com/scientificreports/ our research group that IL-6 is a multifaceted cytokine involved in the control of T. gondii infection in human monocytes and human trophoblastic cells 72,73 . Besides, this cytokine was also associated with the parasite control in infected-villous explants 30,31,33 . Several studies have demonstrated that human trophoblastic cells and human villous explants produce MIF and, this cytokine release has an important role during infection by different parasites, including T. gondii.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…It was demonstrated by www.nature.com/scientificreports/ our research group that IL-6 is a multifaceted cytokine involved in the control of T. gondii infection in human monocytes and human trophoblastic cells 72,73 . Besides, this cytokine was also associated with the parasite control in infected-villous explants 30,31,33 . Several studies have demonstrated that human trophoblastic cells and human villous explants produce MIF and, this cytokine release has an important role during infection by different parasites, including T. gondii.…”
Section: Discussionmentioning
confidence: 92%
“…Several studies have demonstrated that human trophoblastic cells and human villous explants produce MIF and, this cytokine release has an important role during infection by different parasites, including T. gondii. Besides that, this cytokine has a critical function to reduce T. gondii proliferation in maternal-fetal interface 29,31,33,[74][75][76][77] . Thus, based on the literature and our data, we proposed that the modulation of cytokine production in BeWo cells during T. gondii infection by oleoresins is dependent on both the Copaifera species and the concentration of oleoresin used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Assim, várias pesquisas buscam alternativas para o tratamento da toxoplasmose. A azitromicina é um desses tratamentos alternativos que já foi estudada em células de linhagem humana e explantes placentários humanos mostrando eficácia contra a infecção (FRANCO et al, 2014;RIBEIRO et al, 2017;FRANCO et al 2019).…”
Section: Toxoplasmoseunclassified